Investigation of Aluminum State in Some Popular Foods, Which Are Cooked in Aluminum Vessels , Using Spectroscopic Analysis Methods (Latakia University Journal -Basic Sciences Series, 2019)
تم تحديد عنصري الألمنيوم والرصاص في مياه الشرب و المحاليل الملحية للحمص والفول المطهية بأوان مصنوعة من الألمنيوم وأخرى من التيفال وذلك من أجل المقارنة باستخدام مطيافية الامتصاص الذرية المزودة بفرن الغرافيت ( Atomic absorption spectroscopy by graphite Furnace  ) حيث درست العلاقة بين زمن التسخين وكمية الألمنيوم المنتقلة إلى محاليل هذه الأغذية . وقد تم تحديد عنصر الرصاص انطلاقا من الحقيقة القائلة أن هذا العنصر يمكن أن يدخل الى هذه الأواني بشكل أو بآخر أثناء تصنيعها . تشير نتائج هذه الدراسة أن كمية الألمنيوم سجلت أعلى قيمة لها بدون تسخين في المحلول الملحي (17.71 μg / ml) تلاها محلول الحمص (9.95 μg / ml) ثم محلول الفول ( 2.81 µg / ml )عند التسخين لفترة زمنية قدرها 120 دقيقة . وقد سجل عنصر الرصاص تركيزا وسطيا مقداره (0.022 μg / ml) حيث بلغت أقصاها ( 0.63 µg / ml ) في العينات المدروسة مما يدل على دخول هذا العنصر بشكل أو بآخر إلى أواني الألمنيوم أثناء تصنيعها. Aluminum and lead elements were determined in drinking waters and salt solution from chick- pea and faba-bean cooked in aluminum vessels and others from Teflon for comparison using Atomic absorption spectroscopy by graphite furnace. The relationship between heating time and aluminum quantities transferred to these food solutions was investigated. The lead element was determined  taking into consideration  the fact that  this element may enter in these vessels somehow during the  manufacturing process . Results show that : the highest value of aluminum quantities was recorded in salt solution ( 17.022µg /ml ) without heating , followed by chick-pea solution ( 9.95 µg / ml ) , then faba- bean solution ( 2.81 µg / ml ) when the heated period was 120 minutes .